2020
DOI: 10.1155/2020/8855965
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Intestinal Parasites and Their Associated Factors among Diabetes Mellitus Patients at the University of Gondar Referral Hospital, Northwest Ethiopia

Abstract: Background. Worldwide, more than one-sixth of the population is infected by intestinal parasites, of which the majority live in developing countries. On the other hand, the prevalence of diabetes mellitus has been increasing over recent decades in developing countries. Patients with diabetes mellitus encountered impaired immunity and suffer from the consequences of infection particularly intestinal parasitic infection. Objective. This study is aimed at assessing the prevalence of intestinal parasites and assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…The low prevalence could be as a result of improved hygiene practices and or urban settlements in which there are improved social amenities. The prevalence was higher than the prevalence rate of 20.6% obtained by Almugadam et al (2021) which was carried in Sudan, and also higher than 19.2% prevalence reported from Ethiopia by Ambachew et al, (2020). This could be due to different geographical locations, difference in sample size and study population, as well as location and season.…”
Section: Discussioncontrasting
confidence: 63%
“…The low prevalence could be as a result of improved hygiene practices and or urban settlements in which there are improved social amenities. The prevalence was higher than the prevalence rate of 20.6% obtained by Almugadam et al (2021) which was carried in Sudan, and also higher than 19.2% prevalence reported from Ethiopia by Ambachew et al, (2020). This could be due to different geographical locations, difference in sample size and study population, as well as location and season.…”
Section: Discussioncontrasting
confidence: 63%
“…Some similar studies have earlier reported an association between the duration of DM and the aquisition of enteric parasitic infection [14,30]. Tis is contrary to other studies which reported no association between the duration of DM and the acquisition of EPIs [12,36]. Tis might be due to environmental factors and the diferences in the quality of healthcare that exist in the study sites and their infuence on controlling secondary infections in patients with diabetes.…”
Section: Discussioncontrasting
confidence: 57%
“…(18), Ascaris lumbricoides (8), Hookworms(4), Trichuris trichuria (4), Giardia lamblia (6), Teania spp(2) Ambachew et al. [ 28 ] 2020 2018–2018 African region Ethiopia Amhara Stool Formal-ether, microscopic 234 45 Ascaris lumbricoides (15), Entamoeba histolytica/dispar (9), Hookworms (9) Engidaw and Feysa [ 29 ] 2020 2019–2019 African region Ethiopia Debre Tabo NR NR 265 69 IPs Sisu et al. [ 30 ] 2021 2021–2021 African region Ghana Bolgatanga Stool Formal-ether, microscopic 152 19 Giardia lamblia (9), E. histolytica (4), C. parvum (3), Entamoeba.…”
Section: Resultsmentioning
confidence: 99%